Financial Intermediaries and the Yield Curve - Schneider, Andrés (Review of Financial Studies, 2026)
I study the yield curve dynamics in a general equilibrium model with financial intermediaries facing financing constraints. When constraints bind, intermediaries reallocate their portfolios, causing deadweight losses in aggregate consumption, thus affecting savers’ marginal utility. Because the yield curve is a forecast of marginal utility, intermediaries’ constraints show up, via general equilibrium forces, in long-term yields. I show that the mechanism connecting intermediaries’ constraints and long-term yields produces highly nonlinear interest rate dynamics and a positive real term premium in equilibrium. I extend the analysis to the nominal yield curve using a simple Taylor rule.